Emerging trends and research patterns in international branding strategies: A bibliometric analysis / Nor Amira Mohd Ali and Muhammad Hanif Abdul Gafar - Mohd Ali, Nor Amira; Abdul Gafar, Muhammad Hanif (Research Management Centre (RMC), 2023)
This study aims to provide a comprehensive analysis of emerging trends and research patterns in the field of international marketing, specifically on international branding strategies. With the ever-increasing globalization of markets, companies face unique challenges in effectively managing their brands across borders. A bibliometric approach analyzed a diverse range of scholarly publications from reputable sources to identify key themes, research areas, and influential works. The analysis covered a wide range of variables, including document types, source types, publication years, language, subject areas, authorship, institutions, countries, and citation metrics. By utilizing Scopus as the primary data source between the years 1989 to 2022, a comprehensive search was conducted using relevant keywords such as “international marketing,” “branding strategies,” and “global branding”. There were 153 documents selected for further analysis, and standard bibliometric indicators were used to report the documents’ profiles. The researcher used various analytical tools such as Microsoft Excel to calculate the frequency and percentage of published materials, OpenRefine software to standardize keywords, Harzing’s Publish and Perish software to calculate citation metrics, and VOSviewer and WordArt tools to create bibliometric networks and visualizations. The findings revealed several significant trends and patterns contributing to a deeper understanding of key themes, influential works, and emerging research areas. They provide decision makers, guide practitioners, and policymakers with valuable insights for advancing knowledge, making informed decisions, and addressing contemporary challenges in the dynamic realm of international branding strategies. Overall, this comprehensive analysis of emerging trends and research patterns in international marketing sheds light on the evolving landscape of the field.